Multicultural Education and Humanism Theory as An Effort to Improve The Social Sensibility of Primary School Students - Alifah, Pipiet (Jurnal VARIDIKA, 2018)
Data from the Indonesian Child Protection Commission noted that 34%Children deal with the law, one of the cases is bully. The bully case is one proof of thesocial sensitivity of the elementary students. The program for basic education thatcan be pursued to increase social sensitivity is through multicultural education andthe theory of humanism. This study uses a literature study method that collects several reference journals and textbooks. The results of the research are collaborative methods of multicultural-based education and humanism theory when classroom learning is more effective for improving social sensitivity for elementary school students.